Konsep Diri Korban Cyber Sexual Harassment Pada Pengguna Media Sosial Instagram: (Fenomenologi pada Mahasiswa di Surakarta) - Nanda, Karina Tusya; Sekar Wangi, Maya; Mahar Rizqi, Fikriana (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
With social media, users can communicate and interact widely with known people as well aswith new people. Instagram is a social networking platform that allows users to shareinformation in the form of photos or videos with captions attached. One of the crimes on socialmedia is cyber sexual harassment. This research aims to find out the self-concept of cybersexual harassment victims and to understand how cyber sexual harassment victims are in theprocess of self-acceptance after experiencing trauma and how to develop a positive self-concept.This study uses a type of qualitative descriptive research with a phenomenological approach tostudents in Surakarta. The data collection method uses interviews and documentation. Thedata was analyzed.Keywords: Self-Concept, Cyber Sexual Harassment, Instagram, Surakarta Students